Gambaran pengetahuan dan sikap bidan tentang protokol kesehatan Pada antenatal care di masa pandemi covid-19‎ - Siti Khotimah (Jurnal Ilmu Kesehatan Dharmas Indonesia, 2021)
During the Covid-19 Pandemic, midwives must have a good knowledge and attitude about health protocols, especially about antenatal care. This study aimed to determine the knowledge and attitude of midwives in providing midwifery services in accordance with antenatal care health protocols during the Covid-19 pandemic. This study was a descriptive study with total sampling. 35 midwives in the area of ​​Dharmasraya Regency were involved in this study. The sampling process is done online by distributing questionnaires through a link on WhatsApp. The results of the study were: most of the respondents (68.6%) had good knowledge and 82.9% had a positive attitude about the antenatal care health protocol. A good midwife's knowledge and a positive attitude about antenatal care protocols during Covid-19 in providing pregnancy care can improve maternal health and prevent the transmission of diseases caused by Covid-19.